2019
DOI: 10.1016/j.ijso.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical audit on the practice of documentation at preanesthetic evaluation in a specialized university hospital

Abstract: Background:Performing preanesthetic evaluation, documenting, and keeping readily accessible record are responsibilities of anesthetists. Documentation can improve overall patient outcome. It also has an irreplaceable role in medico-legal aspects. Documentation is one of the challenges of providing quality care.Aim:The aim of this study was to evaluate the quality of documentation practice during preanesthetic visits.Materials and Methods:This clinical audit was conducted in the University of Gondar Hospital. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 39 publications
6
23
1
Order By: Relevance
“…The findings are in line with the study conducted by Marco AP et al which shows the completion rate was higher in the group with structured form when non structured and structured forms for preanesthetic evaluation were compared [7]. The study by Woldegerima and et al indicated that the elective procedure with most of the indicators is higher in the elective surgery compared with emergency surgery [17]. In our study, the complete rate was more in the elective surgery compared to emergency surgery.…”
Section: Dicussionsupporting
confidence: 92%
“…The findings are in line with the study conducted by Marco AP et al which shows the completion rate was higher in the group with structured form when non structured and structured forms for preanesthetic evaluation were compared [7]. The study by Woldegerima and et al indicated that the elective procedure with most of the indicators is higher in the elective surgery compared with emergency surgery [17]. In our study, the complete rate was more in the elective surgery compared to emergency surgery.…”
Section: Dicussionsupporting
confidence: 92%
“…Nevertheless, all the professional anesthesia bodies worldwide strongly emphasize that PAR documentation must be adequate and complete as it is important for patient safety, quality assurance and medico-legal purposes. [7][8][9][10][11][12][13][14][15][16] We chose the 'ASA Statement on Documentation of Anesthesia Care' as the standard guideline for comparison with our PAR because its' policy update was more recent as compared to the ANZCA guideline. 8,9 There was a study done previously in an Australian teaching hospital that compared the adequacy of perioperative anesthetic documentation and its' adherence to the Australian guidelines, and found it to be unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…A similar high (92.6%) documentation rate has been reported. 23 Allergic drug reaction accounts for 1:10,000-20,000 in anesthesia, common causative agents include neuromuscular blocking agents, antibiotics and latex. 24 Questioning regarding the last oral intake is a compulsory component of preoperative assessment.…”
Section: Figure 1: Overall Paaf Completion Ratementioning
confidence: 99%
“…This is contrary to previous studies where a very low rate of fasting status was reported. 22,23 This difference could be due to the format of our PAAF where fasting status is written immediately beside the final clearance. This makes documentation of fasting status easy but despite this, competition is less than the acceptable target of our study.…”
Section: Figure 1: Overall Paaf Completion Ratementioning
confidence: 99%